Will UN Article 24 lead to the demise of special education or to its re-affirmation? - Hyatt, Christina; Hornby, Garry (Support for Learning, 2017)
Article 24 of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) contains the first legal enshrinement of the right to inclusive education for people with disabilities. The UNCRPD maintains that children with special educational needs and disabilities (SEND) have a basic human right to be educated in mainstream schools. However, this does not take into account their moral right to receive the education most appropriate to their needs. Therefore, it is asserted by this review that fully implementing Article 24 may not be in the best interest of all children with SEND. Article 24 calls for all countries to implement a fully inclusive education system, thereby rendering special education provision obsolete. This review article provides a critique of this possibility, addressing the issues and practical implications involved.